Development of harmonic suppressed reconfigurable fractal dipole antenna - Hamzah, Shipun Anuar (2014)
The development of compact size reconfigurable harmonic suppressed antenna is crucial in today’s wireless communication system. One set of Harmonic Suppressed Antenna (HSA) and its reconfigurable configuration in the form of fractal dipole antenna that is integrated with the stubs and tapered balun has been designed and tested in this study. The Koch dipoles are double-sided structure while the tapered balun is triangular. Initial design is based on a 0.9GHz linear half-wavelength dipole. The Koch dipole antenna has equal arm lengths of 128mm. These are fabricated on a lossy FR-4 material. Printed fractal dipole antenna is designed to operate at 670MHz. This shows that the linear dipole can be miniaturized by employing Koch curve fractals onto the radiating structure. Fifteen bands reconfigurable antenna were designed to operate within 400MHz to 3.5GHz. However, as the frequency of operation is a low microwave band, the antenna physical size is relatively large. Tapered balun thus significantly enlarged the antenna size. In addition, the far field radiation pattern resembles that of a linear dipole. The overall antenna is found to be large and has moderate gain and efficiency. Nevertheless, it can potentially have higher gain and higher efficiency with the use of a low loss Rogers RT/Duroid material. Thus, the study on the reduction of the tapered balun size is worthwhile. Four sets of wideband tapered baluns with reduced sizes have been designed and tested as a matching circuitry in all the designed antennas. All baluns are found to perform well in terms of scattering parameters and power loss, despite having sizes of 25%, 50% and 75% smaller compared to the original structure. On the other hand, the feeding line method is also investigated. The first design takes into account of 38Ω input impedance of the fractal curve while the second design is a direct connection from the 50Ω SMA connector to terminal. The latter is then selected as it successfully eliminated the antenna’s higher order modes, while the former is suitable for designing an optimum typical dipole antenna. Both antenna and balun are fabricated on Rogers 4530B. Four sets of HSA with reduced size have been designed and tested in this study. All sets were based on the 0.9GHz linear half-wavelength dipole and have equal arm lengths of 132mm. These are named as MFDB, MFDB75, MFDB50 and MFDB25. The antennas operate at 691MHz with low return loss and successfully suppressed their two harmonic frequencies. The MFDB25 antenna is found to exhibit similar performance in terms of the S-parameters and gain. It is also a compact antenna compared to the corresponding proposed HSA structure while the antenna achieved size reduction close to 19.7%, 31.4% and 43.4%. Hence, four sets of harmonic suppressed reconfigurable antennas named TMFDB, TMDB75, TMFDB50 and TMFDB25 have been designed and simulated. The total numbers of switches are 56, 54, 54, and 50 units respectively. TMFDB25 antenna is then fabricated and tested. It is found that the antenna has successfully configured 15 frequency bands and simultaneously suppressed higher order modes. The first prototype of an active TMFDB25 antenna is fabricated to enhance the performance. The suitability of this antenna for space–limited application of future communication system such as cognitive radio has been demonstrated. . The developed antenna can reduce the size of the front-end RF unit, reduce EMI interference and provide another additional characteristic for reconfigurable antenna. Hence the aim of this project has been achieved.